Pubertal development in ALG6 deficiency (congenital disorder of glycosylation type Ic) - Miller, Bradley; Freeze, Hudson H.; Hoffmann, Georg F.; Sarafoglou, Kyriakie (Molecular genetics and metabolism, 2011)
Information on the hypothalamic pituitary ovarian axis in congenital disorders of glycosylation (CDG) females is scarce. Varying hormonal profiles and degrees of virilization in CDG females suggest a spectrum of yet unidentified mechanisms affected by impaired N-glycosylation. We describe an ALG6D woman who completed puberty with normal gonadotropins and testosterone levels, no virilization, and regular menses. Hormonal follow-up of CDG females is necessary to improve our understanding of the role of glycosylation in pubertal development.
Gesehen am 19.08.2022